(untitled) (Religious dialogue and cooperation, 2021)
Today, as a result of the failure of socialism, we are facing a period of numerous big changes in society, which are of economic, political and social nature. In addition, these changes are accompanied by changes in the value priorities of the social value system. More precisely, people are exposed to influences of social, political and cultural events, so it is difficult for them to adapt. In such a situation, religion offers a philosophy of life that is compatible to specific confession. Ethnicity and religion are basic cohesive factors in multicultural and multiconfessional areas like ours. There are tendencies of individuals and groups to equate nationality with religion. Religion as one of the key factors of human consciousness influences not only the building of spiritual system and the social value system, but also the way of life. Losing self-confidence in solving the important tasks in life, man tries to find help, and it is precisely religion that is the right direction to look for it. It is very important to emphasize the activities of the confessional communities which insist on attracting attention with their organizational structures and filling the gaps that other social institution and organization left empty. The social changes occurring in the late 1980s and early 1990s brought about by the failure of socialism are changing the social role of religion. We live in a world characterized by processes of desecularization or sacralization. The percentage of those who have declared themselves non-religious in the past is almost equal to those who have declared themselves religious in the period after the 1990s. This reversal or change of attitude towards religion, which is characterized by increased religiosity among the entire population, is an inspirational ground for the study of religion. In this research, the subject of investigation was the religiosity of the population in the Ohrid-Struga region, a region that represents ethnic and religion heterogeneous environment. The two most important religious organizations are the Macedonian Orthodox Church - the Ohrid Archbishopric and the Islamic Religious Community. The target group is consisted of people older than 18. The results obtained by the research show the influence of religiosity, which is at a very high level, on the value orientations of the population in the Ohrid-Struga region.